Al-Ta’wīlāt al-Najmiyyah dalam Tafsir Sufistik Persia: Najm al-Dīn al-Kubrā dan ‘Alā’ al-Dawlah al-Simnānī - Supranggono, Zerlinda Prasanti; Ratri Diah Sulistyaningtyas (Journal of Islamic Scriptures in Non-Arabic Societies, 2026)
This study addresses the limited scholarly attention given to the development of Qur’anic exegesis in non-Arab Muslim intellectual traditions, particularly within the Persian Sufi milieu. It focuses on At-Ta’wīlāt al-Najmiyyah, a major mystical commentary associated with the Kubrawiyyah order, which reflects a distinctive mode of Qur’anic interpretation shaped by spiritual discipline, esoteric insight, and non-Arab scholarly transmission. Although widely recognized in the tradition of Sufi tafsīr, its epistemological foundations and interpretive structure remain underexplored in contemporary Qur’anic studies. The aim of this research is to examine the methodological foundations, theological orientation, and hermeneutical framework of At-Ta’wīlāt al-Najmiyyah, while situating it within the broader context of non-Arab Qur’anic exegesis. This study employs a qualitative descriptive method based on textual analysis and Sufi hermeneutics. The primary data are drawn from At-Ta’wīlāt al-Najmiyyah and relevant scholarly works on Kubrawiyyah teachings and Sufi exegesis. The findings show that At-Ta’wīlāt al-Najmiyyah represents an important expression of Persian Sufi tafsīr rooted in the spiritual teachings of Najm al-Dīn al-Kubrā and further systematized by ‘Alā’ al-Dawlah al-Simnānī. The commentary approaches the Qur’an as a text with both outward and inward dimensions, accessible not only through linguistic and rational analysis but also through spiritual purification and inner experience. This study argues that the work significantly contributes to understanding the production, transmission, and diversity of Qur’anic interpretation beyond the Arab intellectual sphere.